Linguistic and functional cognitive peculiarities of media language as the basis of interpretations in the communicative sphere - Olga D. Vishnyakova; Natalia V. Polyakova (Peoples' Friendship University of Russia (RUDN University), 2017)
The study deals with linguistic and functional cognitive aspects of language use in the media with a focus on typical actualisation of linguistic units in continental European business and political press which contain borrowings from the English language alongside original words and collocations, vividly shown by the examples taken from French sources. In the course of communication, the problem of transferring and understanding information arises, thus involving pragmatic and functional cognitive aspects of research. This raises the problem of notions and concepts, particularly in differentiating between strict logical mental structures and formations possessing both logical and sub-logical bases that deal with emotional and evaluative characteristics subject to various interpretations, which is vividly shown in the analysis of the English examples.